2017
DOI: 10.3389/fpls.2016.02042
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Amendment with Fresh and Composted Solid Olive Mill Waste on Olive Grove Affects Carbon Sequestration by Prunings, Fruits, and Soil

Abstract: The soil amendment with organic wastes represents a way to increase the soil fertility and the organic carbon (C) stored in the agro-ecosystems. Among the organic waste materials produced by agricultural and industrial activities, olive mill wastes derived from the olive oil extraction process may represent a suitable soil amendment. The aim of the study was to evaluate the effect of fresh (SOMW) or composted mixture of SOMW and shredded olive tree prunings (C-SOMW+P) on the vegetative and productive activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 49 publications
3
31
1
1
Order By: Relevance
“…In Portugal, this industry produces N600,000 t of wastes, whose discharge without treatment would have a negative impact in the environment. Due to the high content in phosphorous, potassium and organic matter, these wastes have been applied as amendment on the agricultural soils, not only because of its low cost but also for its potential to enhance soil fertility and reduce the risks of soil degradation (Federici et al, 2017;Regni et al, 2017). On the other hand, these wastes contain high amounts of organic substances (fibers, sugars, volatile fatty acids, polyalcohols, pectins and fats) and a variety of phenolic compounds such as hydroxytyrosol and tyrosol, secoiridoid derivatives, phenolic acids and flavonoids (Papaioannou et al, 2013), thus being also a promising source of valuable compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, this industry produces N600,000 t of wastes, whose discharge without treatment would have a negative impact in the environment. Due to the high content in phosphorous, potassium and organic matter, these wastes have been applied as amendment on the agricultural soils, not only because of its low cost but also for its potential to enhance soil fertility and reduce the risks of soil degradation (Federici et al, 2017;Regni et al, 2017). On the other hand, these wastes contain high amounts of organic substances (fibers, sugars, volatile fatty acids, polyalcohols, pectins and fats) and a variety of phenolic compounds such as hydroxytyrosol and tyrosol, secoiridoid derivatives, phenolic acids and flavonoids (Papaioannou et al, 2013), thus being also a promising source of valuable compounds.…”
Section: Introductionmentioning
confidence: 99%
“…e different residues from the wine industry are characterized by low pH and electrical conductivity and high organic matter content [7]. e richness of these by-products in organic matter allows their use for soil fertility improvement [8,9]. e direct incorporation of these residues could cause serious environmental problems if they are added excessively to the soil in an uncontrolled manner.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shown that composting is one of the effective alternatives for the recycling and the valorization of organic wastes [8,[17][18][19][20][21][22]. It is a degradation process of the organic matter, allowing the achievement of a stable product, rich in humic substances and in fertilizing elements, serving as soil organic amendment [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-row cover cropping, retention of on-farm sources of organic matter (e.g., prunings), and application of off-farm sources of organic matter (e.g., composts and organic mulches) all can potentially increase soil organic carbon (SOC) stocks in perennial fruit cropping systems [19,20]. For example, amendments with olive mill waste have been reported to improve carbon sequestration in soils and improved N, P, and K availability in olive groves [21]. The use of fescue (Festuca arundinacea Schreb) has been reported to increase soil organic carbon and microbial biomass C in grapes [22].…”
Section: Soil Carbonmentioning
confidence: 99%